The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1080/02652039009373912
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of aflatoxins in mustard and mustard products

Abstract: Natural occurrence of aflatoxins at concentrations of 750, 87 and 1420 micrograms/kg was recorded in 44, 33 and 80 samples out of 100 samples each of seeds, oil and cakes of mustard respectively. Out of 17 species of fungi isolated from mustard seeds, percentage incidence of the Aspergillus flavus group was maximum during monsoon and summer. Twenty-five per cent of isolates (out of 1143 isolates screened) of the A. flavus group were toxigenic, producing different components of aflatoxins in varying concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The presence of aflatoxin B1 in sunflower oils and mustard suggests that this mycotoxin could be present in sunflower and grapeseed meals [132,133]. In the same way, because zearalenone was found in rapeseed and maize oils it could also be present in the meals, but probably at a lower concentration than that observed in maize [131].…”
Section: Mycotoxin Contaminationmentioning
confidence: 99%
“…The presence of aflatoxin B1 in sunflower oils and mustard suggests that this mycotoxin could be present in sunflower and grapeseed meals [132,133]. In the same way, because zearalenone was found in rapeseed and maize oils it could also be present in the meals, but probably at a lower concentration than that observed in maize [131].…”
Section: Mycotoxin Contaminationmentioning
confidence: 99%
“…The presence of mycotoxins has been reported in several vegetable oils around the world (Samarajeewa et al, 1983;Bordin et al, 2014). Aflatoxins have been reported in olive oils in Greece by Papachristou and Markaki (2004) and in Spain and Morocco by Cavaliere et al (2007) elsewhere in North Africa, in peanut oil in Senegal and China by Bao et al (2010) and in mustard oil, used for cooking in Northern India at concentrations of 55 to 87 ppb (Sahay and Prasad, 1990). The presence of aflatoxins in peanut oils is worrying.…”
Section: Mycotoxins In Edible Oilsmentioning
confidence: 99%
“…Mustard is a susceptible substrate for aflatoxin contamination (Sahay and Prasad, 1990;Bilgrami et al, 1991). Bilgrami et al, (1991) found mustard seeds of preharvested crops to be contaminated with various levels of aflatoxin.…”
Section: Other Spices and Herbsmentioning
confidence: 99%